Road trip to nowhere : Hollywood encounters the counterculture - Lewis, Jon, 1955- (University of California Press, 2022)
"By 1967, the commercial and political impact on Hollywood of the 'sixties' counterculture had become impossible to ignore. The studios were in bad shape, still contending with a generation-long box office slump and struggling to get young people into the habit of going to the movies. Road Trip to Nowhere examines a ten-year span (from 1967-1976) rife with uneasy encounters between artists caught up in the counterculture and a corporate establishment still clinging to a studio system on the brink of collapse. Out of this tumultuous period many among the young and talented walked away from celebrity, turning down the best job Hollywood (and America) had on offer: movie star. Road Trip to Nowhere elaborates a primary-sourced history of movie production culture, examining the lives of a number of talented actors who got wrapped up in the politics and lifestyles of the counterculture. Thoroughly put off by celebrity culture, actors like Dennis Hopper, Christopher Jones, Jean Seberg, and others rejected the aspirational backstory and inevitable material trappings of success, much to the chagrin of the studios and directors who backed them. In Road Trip to Nowhere, distinguished film historian Jon Lewis details dramatic encounters on movie sets and in corporate boardrooms, on the job and on the streets, and in doing so offers an entertaining and rigorous historical account of an out-of-touch Hollywood establishment and the counterculture workforce they would never come to understand"--